THE INFLUENCE OF KOREAN DRAMA STORYLINE ON EMOTIONAL ESCAPE IN GENERATION Z AGED 18-23 YEARS (STUDY AT RW 06 GUNTUR, SETIABUDI, SOUTH JAKARTA) - Anju Kimberley Silalahi; RR. Roosita Cindrakasih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to determine and measure the influence of Korean drama storylines on emotional escape among Generation Z aged 18-23 years in RW 06, Guntur, Setiabudi, South Jakarta. The Korean Wave phenomenon, which has become increasingly widespread in the era of digital streaming, has made Korean dramas one of the most popular forms of entertainment among Generation Z, often serving as a means of emotional escape from academic, social, and work-related pressures. This research employed a quantitative approach with an explanatory survey design and was grounded in the Stimulus-Organism-Response (S-O-R) theory, in which Korean drama storylines were positioned as the stimulus and emotional escape as the response. A sample of 143 respondents was determined using the Slovin formula and selected through purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using simple linear regression with the assistance of SPSS version 27. The results showed the regression equation Y = 4.006 + 0.673X, with a t-value of 10.954 and a significance level of < 0.001, indicating that was rejected and was accepted. The coefficient of determination () was 0.460, indicating that Korean drama storylines explained 46.0% of the variance in emotional escape, while the remaining 54.0% was influenced by other factors outside the scope of this research model.